Letter from Svante Arrhenius to Georg Bredig, July 1908 - Arrhenius, Svante (1908)
Svante Arrhenius (1859-1927) writes about his new assistant Taylor, an American who studies fermentation, reactions of acids, and agglutination. Arrhenius also praises Georg Bredig (1868-1944) on his work Old and New Topics in Catalysis .
Keywords: Scientists; Chemists; Chemistry; Arrhenius, Svante, 1859-1927; Bredig, Georg, 1868-1944; Agglutination